Prevalence and factors associated with anemia among pregnant women during the COVID-19 pandemic in East Lombok district, Indonesia - Amanda Safiera Ameline; Dian Novita Chandra; Min Kyaw Htet; Nur Lailatuz Zahra; Umi Fahmida (PLoS ONE, 2025)
Background Maternal anemia is a major public health problem that has detrimental effects on pregnancy and birth outcomes. The threat of food insecurity and nutritional deficiencies is growing as a result of the COVID-19 pandemic. The aim of this study was to determine the prevalence and risk factors of anemia among pregnant women in East Lombok during the pandemic. Materials and methods This community-based cross-sectional study is part of an observational cohort study entitled “UKRI-GCRF Action Against Stunting Hub (AASH)” in rural areas of East Lombok, Indonesia. Data were collected from women (18–40 years) in their third trimester pregnancy (N = 446) from June 2021 to January 2022. Data collection included hemoglobin, mid-upper arm circumference, intestinal helminth infections, and structured questionnaires for sociodemographic, dietary diversity, pregnancy-related, food security (US-HFSSM), reduced coping strategy index (rCSI), and COVID-19-related variables. The association between anemia and its determinants was analyzed using binary logistic regression model. Results Anemia was found in 40.8% of pregnant women in third trimester. During the pandemic, 74.7% and 28.9% of women reported a decrease in household income and food expenditure whereas 47% of them reported having medium-to-high coping strategies. The proportion of women who had chronic energy deficiency (CED), inadequate dietary diversity, non-use of contraceptives was 10.5%, 28.3%, and 38.8%, respectively. In logistic regression, anemia was significantly associated with CED (AOR = 1.92; 95%CI: 1.06–3.48), inadequate dietary diversity (AOR = 1.58; 95%CI: 1.02–2.45), and non-use of contraception (AOR = 1.58; 95%CI: 1.02–2.45). Conclusions The prevalence of maternal anemia was high in the study area, and it was associated with CED, inadequate dietary diversity, and non-use of contraception. The findings highlight the importance of improving anemia control programs among pregnant women through nutrition education focusing on food based dietary recommendations, and conditional cash transfer which include family planning and compliance of iron folic acid to strengthen their resilience to natural phenomenon such as COVID-19 in rural areas like East Lombok.